1983
DOI: 10.1128/aem.46.4.846-854.1983
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium-resistant bacteria isolated from river sediments

Abstract: Hexavalent chromium [Cr(VI)] is a known carcinogen and mutagen; however, the actual mechanisms of Cr toxicity are unknown. Two approaches were used to isolate Cr(VI)-resistant bacteria from metal-contaminated river sediments. Diluted sediments were plated directly onto a peptone-yeast extract (PYE) medium containing 0 to 100 ,ug of Cr(VI) ml-'. Approximately 8.4 x 105 CFU g-1 were recovered on 0 ,ug of Cr(VI) ml-', whereas 4.0 x 102 CFU g-1 were recovered on PYE plus 100 ,ug of Cr(VI) ml-1. Alternatively, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…T h e highest incidence of metal antibiotic double resistance exists between: zinc and ampicillin (50°/o); lead and all antibiotics (10Oo/o); copper and penicillin (95%); cobalt and ampicillin (50%); cadmium and erythromycin (25.9%); nickel and ampicillin (83.3%); mercury and bacitracin (73.7%); and finally arsenic and gentamicin (81.5%). T h e resistance to a particular heavy metal has been correlated to antibiotics and other heavy metal resistance in a variety of organisms (Austin and Colwell 1977;Luli et al 1983) and the role of plasmids in confering resistance to both antibiotics and metals has been previously demonstrated (Foster 1983;Lyon and Skurray 1987).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…T h e highest incidence of metal antibiotic double resistance exists between: zinc and ampicillin (50°/o); lead and all antibiotics (10Oo/o); copper and penicillin (95%); cobalt and ampicillin (50%); cadmium and erythromycin (25.9%); nickel and ampicillin (83.3%); mercury and bacitracin (73.7%); and finally arsenic and gentamicin (81.5%). T h e resistance to a particular heavy metal has been correlated to antibiotics and other heavy metal resistance in a variety of organisms (Austin and Colwell 1977;Luli et al 1983) and the role of plasmids in confering resistance to both antibiotics and metals has been previously demonstrated (Foster 1983;Lyon and Skurray 1987).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…An increase in the tolerant fraction vis-a-vis a heavy metal has been reported in a number of studies on the effect of heavy metal addition in soil microcosms 5,6,16,19,29,30,32) and heavy metal polluted environments 11,14,18,27,31) . Díaz-Ravińa et al 6) for example, examined the development of metal tolerance in soil bacterial communities exposed to different heavy metals (Cu, Cd, Zn, Ni, and Pb) under laboratory conditions by thymidine incorporation and plate count tech-niques.…”
Section: Discussionmentioning
confidence: 82%
“…ple, Cr 16) , Cu 38) , and Hg 30) contamination. The Tl-tolerant bacteria isolated in this study were identified as several groups in the Alphaproteobacteria, Pseudomonas, and Bacillus (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Resistance of the bacterial isolates to varying concentrations of zinc was determined by agar dilution method [ 16 ] . Fresh overnight cultures of the isolates grown in peptone water were aseptically inoculated into nutrient agar plates, which were supplemented with increasing concentration of zinc metal ions (500 m g/ml-1.5 mg/ ml).…”
Section: Bacterial Zinc Resistance Testmentioning
confidence: 99%